The motion of spinor in the vicinity of spherical star and the magnetic field of non-homogeneous spherical bodies - Minister, Samson Adigizi; Chifu, Ebenezer Ndikilar (Universitas Sebelas Maret, 2024)
In this article, we developed the spinors connections from Schwarzschild metric and make use of the spinor connections in geodesics in order to obtain the equation of spinor in the vicinity of spherical star. The gravitational scalar potential for non-homogeneous spherical body was use to developed the magnetic field of different regions of some non-homogenous spherical bodies.